Acute Generalized Exanthematous Pustulosis Due to Labetalol Drug Fever and Leukocytosis Caused by Tigecycline Toxic Hepatitis Induced by Methylprednisolone Intravenous Pulse Dosing Mitoxantrone-Related Osteonecrosis of the Jaw Medications with Anticholinergic Effects and Their Implications in the Elderly. Issue 6 (June 2016) - Mancano, Michael A.
The purpose of this feature is to heighten awareness of specific adverse drug reactions (ADRs), discuss methods of prevention, and promote reporting of ADRs to the US Food and Drug Administration's (FDA's) MEDWATCH program (800-FDA-1088). If you have reported an interesting, preventable ADR to MEDWATCH, please consider sharing the account with our readers.